UNDERSTANDING VERTICAL HOLINESS AS A RECEIVED BUSINESS ON UNDERPASS DEVELOPMENT - Wibawa, I Made Sastra; Redana, I Wayan; Suthanaya, Putu Alit; Wiryasa, Ngakan Made Anom (International Journal of Engineering and Emerging Technology; Vol 5 No 1 (2020): January - June, 2020)
Development efforts in the vertical direction should have been better than in the horizontal direction which only requires land to the side. The emergence of new ideas certainly raises the pros and cons, most local geniuses are vertical purity, the compilation passes under the terraced infrastructure there is a feeling of flare/fatigue because it is bypassed by people. The aim of the study is to reveal the vertical relationship with the design of underpasses, and how community acceptance of underpass construction. The methodology used is complicated through interviews with Hindu scholars, Bali, which are then used as a basis for further observation for shareholders so that questionnaires can be prepared. The results of the questionnaire are data of the relationship between vertical and attitude of community acceptance towards underpass development. The data obtained were analyzed by Logistic Regression. The results of the study of vertical simplicity are local wisdoms that need to be discussed and agreed in this modern era. Furthermore, the results of the analysis show that there is a relationship between vertical purity and uneven plot intersection height, as evidenced by the acceptance of the hypothesis at the significance level ? = 0.05. The results of the analysis show "significance <?" or (0.033 <0.05), this means vertical purity, which means significant effect on underpass height design. Alternative designs also need to reduce underpass differences. Invitations are made very necessary as a legal umbrella for the design and manufacture of underpasses. Keywords: Vertical purity, underpass, cemer/leteh , alternative design .